2011
DOI: 10.1111/j.1526-4610.2011.01966.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurostimulation for Primary Headache Disorders, Part 1: Pathophysiology and Anatomy, History of Neuromodulation in Headache Treatment, and Review of Peripheral Neuromodulation in Primary Headaches

Abstract: Neurostimulation for primary headaches is being increasingly utilized as a treatment modality. Use of neuromoduation has generated multiple case reports as well as some controlled studies. This article is the first of 2 systematic reviews of available data regarding neurostimulation for primary headache conditions. The pathophysiology, relative anatomy, theoretical mechanisms, and history of neurostimulation for primary headache are covered in this section, Part 1 of 2. The literature regarding peripheral neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 60 publications
0
43
0
Order By: Relevance
“…14,17,18,20 It has been well established that ONS has excellent efficacy for the treatment of occipital neuralgia or occipitally localized pain with an average of 88% of individuals attaining greater than 50% pain relief. 7,11,16,23 However, when ONS is used to treat primary headache such as cluster headache and CM, the effect has been less than ideal, with a total of 54% patients with cluster headaches and 47% with migraine headaches responding to the treatment, according to the comprehensive reviews of neurostimulation for primary headache disorders by Jenkins and Tepper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,17,18,20 It has been well established that ONS has excellent efficacy for the treatment of occipital neuralgia or occipitally localized pain with an average of 88% of individuals attaining greater than 50% pain relief. 7,11,16,23 However, when ONS is used to treat primary headache such as cluster headache and CM, the effect has been less than ideal, with a total of 54% patients with cluster headaches and 47% with migraine headaches responding to the treatment, according to the comprehensive reviews of neurostimulation for primary headache disorders by Jenkins and Tepper.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout this "traditional" period the clinical approach has always been to produce a paresthesia over the parts of the body that hurt, which indicated that the correct portion of the nervous system was being stimulated. 7,15 Migraine is more commonly experienced in the frontotemporal area innervated by the trigeminal nerve rather than in the occipitocervical area innervated by the greater occipital nerve; thus, for the neurostimulator to work, the paresthesia induced needs to cover the affected area. 15 With ONS alone, most of the migraine-affected area of pain is insufficiently covered.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, prevention strategies are important components of therapy aimed at reducing the attack frequency and severity. Several drugs have been evaluated for use in the treatment (or prevention) of headache 2,3 as well as nonpharmacological treatments, [5][6][7] all with varying degrees of success.…”
Section: Introductionmentioning
confidence: 99%
“…The references are of perhaps greater interest, with Leone proposing a template for patient selection, Fontaine providing the only true sham controlled study, and Jenkins and Tepper giving this readership a wonderful prior review of neurostimulation in primary headache disorders. 1‐4 …”
Section: Headache Gallimaufrymentioning
confidence: 99%